Comparative economics of spray scheduling for the management of late leaf spot of groundnut incited by Phaeoisariopsis personata - A.P. SURYAWANSHI, ANUP DAS and S.P. DAS, UTPAL DEY*, D.N. DHUTRAJ (Indian Phytopathology, 2016)
Late leaf spot (LLS), caused by Phaeoisariopsis personata, a foliar disease of groundnut or peanut (Arachis hypogaea) is one of the important factors limiting groundnut productivity in India. It frequently inflicts colossal yield losses of more than 50% on unsprayed peanuts. The current studies emphasized upon the management strategies to mitigate the losses caused by the disease. Among the fungicides, Difenoconazole (@ 0.1%) recorded the highest pod yield (1757 kg/ha) and test weight (30.75 g) with least disease incidence (17.98%), severity (12.30%), minimum defoliation (4.83%), minimum frequency (1.20/mm2) and reduced size (1.31 mm2) and thereby increased the pod yield by 53.04 per cent and test weight by 21.79 per cent over unsprayed control followed by Propiconazole (@ 0.1%) which recorded pod yield of 1649 kg/ha and test weight of 29.90 g with disease incidence (19.53%), severity (16.58%) and minimum defoliation (5.66%) and thereby increased the pod yield by 49.97 per cent and test weight by 19.57 per cent over unsprayed control. Both the botanicals (Mehandi @10% and NSKE @ 5%) and bioagents (Trichoderma viride, Verticillium lecanii and Bacillus circulans @ 5%) recorded significantly higher pod yield (range, 1089-1333 kg/ha) and test weight (range, 24.39-26.88 g) and increased the pod yield (range, 21.88-38.11%) and test weight (range, 1.39-10.53%) over unsprayed control (yield 825 kg/ha and test weight 24.05 g). The late leaf spot disease incidence and defoliation were found to be reduced with increased number of (two-three) sprayings of the fungicides.